Evaluating Transperineal Laser Ablation as a Minimally Invasive Therapy for BPH: A Systematic Review and Meta-Analysis - Amalia Intan Marhendrati; Nanda Daniswara (Eduvest - Journal of Universal Studies, 2025)
Benign prostatic hyperplasia (BPH) is a common illness in older men, marked by lower urinary tract symptoms (LUTS) that diminish quality of life. Although conventional therapies like medication and transurethral resection of the prostate (TURP) are effective, they frequently entail considerable adverse effects. Transperineal Laser Ablation (TPLA) has emerged as a viable minimally invasive surgical intervention that provides symptom alleviation with potentially reduced consequences. The objective of this study is to comprehensively assess the clinical effectiveness and safety of TPLA in the treatment of BPH through the analysis of aggregated data from previous cohort studies. A systematic review and meta-analysis were performed in accordance with PRISMA recommendations. A total of 449 people were enrolled across ten trials. The meta-analysis revealed a substantial enhancement in all evaluated outcomes following TPLA: a −58.435% decrease in IPSS (95% CI: −70.421 to −46.449), a −63.937% reduction in PVR (95% CI: −76.937 to −50.938), a +68.031% increase in Qmax (95% CI: 47.438 to 88.624), and a −27.927% decline in prostate volume (95% CI: −36.575 to −19.280). Significant heterogeneity (I² > 90%) was observed across all outcomes. Discussion: The results indicate that TPLA markedly improves both subjective symptoms and objective urine function in individuals with BPH. TPLA is a promising, minimally invasive procedure for BPH, showing significant improvements in symptom severity and urine parameters. Although existing data endorse its effectiveness and safety, forthcoming randomized controlled studies are important to validate its long-term results and define its position in clinical practice.